Workers fired for reasons pregnancy and their rigth to social security as a precautionary measure in Mexico - Jiménez Juárez, Carla (2023)
Mexico has a national, international and jurisprudential legal framework that protects pregnant and breastfeeding workers, who enjoy a special privilege called reinforced labor stability, which implies their right to remain in their jobs and their right to social security. The labor reform of May 1, 2019 recognizes the duty of the labor courts to issue precautionary measures to guarantee the access to social security that a worker unjustifiably dismissed due to her pregnancy had been enjoying. The Supreme Court of Justice of the Nation (SCJN) and the Collegiate Circuit Courts have issued criteria regarding the precautionary measures that labor courts must decree in order to guarantee the right to social security of the pregnant worker, such as access to medical services.